Genetic testing in children with surfactant dysfunction. Issue 7 (26th April 2013) - Turcu, Simona; Ashton, Emma; Jenkins, Lucy; Gupta, Atul; Mok, Quen
Abstract : Objectives: To present the UK experience in genetic diagnoses of surfactant protein dysfunction disorders and develop a referral algorithm for neonates and children with persistent respiratory problems. Materials and methods: Between 2006 and 2011, 427 cases were referred for surfactant mutation analyses to the North East Thames Regional Molecular Genetics Laboratory at Great Ormond Street Hospital, London. The results were reviewed and referring physicians of mutation positive cases contacted to complete a questionnaire providing clinical, radiological, histological and outcome information. Results: 25 new cases were found to have genetic mutations for surfactant dysfunction disorders (7.5%), with six resulting in surfactant protein B dysfunction, seven surfactant protein C dysfunction and 12 ATP-binding cassette subfamily A member 3 (ABCA3) dysfunction. The referrals were from 15 different paediatric centres. In addition, three affected surfactant protein B (SFTPB) cases were prenatal diagnoses, following the birth of previously affected children. The majority of the confirmed cases (23 of 25) were born after 37 weeks gestation. All children with SFTPB dysfunction and the majority of ABCA3 patients presented with respiratory distress at birth. All SFTPB cases died from intractable respiratory failure. The outcome for ABCA3 mutations was variable with seven survivors. The clinical and radiological presentation of surfactant protein C (SFTPC) patients suggested mainly interstitial lung process with the majority surviving on medication. Conclusions: Surfactant mutation analysis is now well established in the UK and allows better genetic diagnosis and counselling. The rarity of the condition makes it difficult to develop a validated algorithm for genetic evaluation with a need for international networking. Referrals need to be rationalised for the service to be time and cost effective.